Pengaruh Diklat (Pendidikan dan Pelatihan) Terhadap Prestasi Kerja Karyawan Di Bank BPR Rokan hulu - Seprini., Nuraisyiah, Hidayat, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This study aims to see how the implementation of education and training, employee performance and the impact of training on employee performance in BPR Rokan Hulu. The research sample using sampling techniques saturated (census), with a total of 32 people. Analysis of data using simple linear regression obtained yield was 0.712, indicating a strong relationship between education and training (education and training) with employee performance, as well as a positive effect. The result of the calculation of the coefficient of determination is 39.6%, which means that the training (education and training) affect the work performance of 39.6%, while the remaining 60.4% is influenced by other variables not examined in this study. From the calculation results of hypothesis testing showed t_hitung greater than T_ (table) that T_ (count) 4.438> 1.697 so the hypothesis that there is a significant impact training (education and training) on employee performance is acceptable.